Digital Capabilities and Risk Management Practice in Small Accounting Firms in Malaysia - Taib, Azuraidah; Awang, Yunita; Said, Jamaliah; Akhir, Noor Erni Fazlina Mohd (Advances in Social Sciences Research Journal, 2024)
Today’s business environment can be described as extremely turbulent and unpredictable due to numerous factors such as social, political and technological changes. Small and medium enterprises (SMEs) are no exception. The situation requires employers and employees to achieve a certain level of technological capabilities and innovativeness. Thus, this digital revolution brings about change, especially in risk management. This study, therefore, seeks to investigate the relationship between digital capabilities and enterprise risk management practice (ERMP) among small accounting firm owners in Malaysia. Online questionnaires were distributed to 341 accounting firm owners and top management who registered with the Malaysian Institute of Accountants database. 290 small accounting firm owners participated in this study. The results show a positive moderate relationship among digital capabilities variables (human, collaborative, innovation and technical capabilities) with the ERMP. However, only innovation capabilities significantly influence the ERMP in small accounting firms in Malaysia. The study is subject to limitations as only one sector of SME from the accounting industry has been examined and only focuses on digital capabilities as a factor that influences ERMP.